Pengaruh Price Earning Ratio, Price to Book Value, Percentage of Shares Offered dan Company Size Terhadap Underpricing Saham Pada Perusahaan Sektor Energi Yang Melakukan IPO Periode 2017-2024 - Nurjanah, Nurjanah; Aisyah Aris Setianingsih; Fakhrizal (FEBI IAIN Langsa, 2024)
The purpose of this study is to determine the effect of price earning ratio, price to book value, percentage of shares offered and company size on underpricing. The data collection method in this study is documentation. This research is a quantitative descriptive and the data used in this study is secondary data. The data used in this study was obtained from secondary data taken from the Indonesia Stock Exchange. The data used consists of financial statements and prospectuses of energy sector companies that conduct IPOs for the 2017-2024 period. The data collection techniques used in this study are through literature studies and documentation. The data analysis techniques used in this study are classical assumption tests, multiple linear regression analysis and correlation analysis. The results of the study show that partially the variables price earning ratio, price to book value, percentage of shares offered have a positive and significant effect on the underprising of company shares while the company size variable has no effect and is significant on the underpricing of shares in energy sector companies that conduct IPOs. Simultaneously, the price earning ratio, price to book value and percentage of shares offered and company size have a positive and significant effect on the underpricing of shares in energy sector companies that conduct IPOs and have a determination value (R2) of 0.936 or 93.6%.